Parental Social Support and Psychological Well-being of Young Adults in Interfaith Dating - Sakerebau, I.E.P. Ombaga; Huwae, Arthur (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Parental social support is understood as emotional, instrumental, esteem, and informational assistance provided by parents to children in the context of interfaith dating relationships. This study aims to analyze the relationship between parental social support and psychological well-being in young adults in interfaith dating relationships in Indonesia. Psychological well-being was measured using Ryff's psychological well-being scale consisting of six main dimensions, namely self-acceptance, positive relationships with others, autonomy, environmental mastery, purpose in life, and personal growth. The research method used was quantitative with a correlational design, with 208 young adult participants in interfaith dating relationships. The results showed a significant positive relationship between parental social support and psychological well-being (r = 0.493, p <0.01). The average parental social support received was 115.16, in the moderate category with a percentage of 56.25% of participants. The average psychological well-being was 84.36, also in the moderate category with a percentage of 57.21%. Parental social support was also positively related to each dimension of psychological well-being. These findings underscore the importance of parental social support in maintaining the psychological well-being of young adults facing challenges in interfaith relationships.